A STUDY OF SYMPTOMATOLOGY OF CONVERSION DISORDER IN PATIENTS REPORTING AT AYUB TEACHING HOSPITAL - Yousafzai, Aziz -ur-Rehman; Irfan, Naveed (Journal of Ayub Medical College Abbottabad, 2000)
Background: The symptomatology of conversion disorder differs from population to population depending upon the local taboos and rituals. This study was carried out to look for the commonest presenting symptoms of conversion disorder in the patients attending psychiatry unit of Ayub Teaching Hospital. No such study was done here in the past. Methods: 100 consecutive patients of either sex, presenting with Conversion disorder in the Psychiatry Department of Ayub Teaching Hospital, Abbottabad, were included in the study. The diagnosis was made observing criteria set by DSM-IV for diagnosis of conversion disorder. Results: 35 % patients reported with Pseudoseizures, 16 % with Paralysis, 12 % with Tremor, 8 % with Aphonia, 6 % each with Gait disorders and Difficulty in swallowing, 5 % each with Mutism and Headache/Pain. 4 % with Blindness and 3 % with Anaesthesia. Conclusions: The results and their comparison with contemporary studies reflect that presenting symptoms of conversion disorder are significantly different from elsewhere.